2012
DOI: 10.5047/eps.2011.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term behavior of annual and semi-annual S q variations

Abstract: We have examined the long-term behavior (solar-cycle time scale) of annual and semi-annual S q variations. We analyzed geomagnetic data observed at locations that were roughly geographically conjugate in the west Pacific region (Kakioka and Gnangara) during the last five solar cycles . Three-year compound data were constructed for each station for each year. The stationary component {S q } 0 , annual component {S q } 1 , and the semi-annual component {S q } 2 , of the S q variations were derived from the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…These results show that the geomagnetic activity (described by Ap) is strongly linked to the solar cycle phase (solar activity is described by F10.7) and in this study, we were unable to exclude variations in foF2 related to geomagnetic activity. Analyzing geomagnetic data observed at Kakioka (Japan) and Gnangara (Australia) over almost five solar cycles, Yamazaki and Yumoto (2012) recently found that solar activity controls not only the stationary component of the geomagnetic solar quiet daily variation field (S q ) but also the annual and semi-annual components. They report that all three components have a positive linear correlation with sunspot numbers.…”
Section: Resultsmentioning
confidence: 99%
“…These results show that the geomagnetic activity (described by Ap) is strongly linked to the solar cycle phase (solar activity is described by F10.7) and in this study, we were unable to exclude variations in foF2 related to geomagnetic activity. Analyzing geomagnetic data observed at Kakioka (Japan) and Gnangara (Australia) over almost five solar cycles, Yamazaki and Yumoto (2012) recently found that solar activity controls not only the stationary component of the geomagnetic solar quiet daily variation field (S q ) but also the annual and semi-annual components. They report that all three components have a positive linear correlation with sunspot numbers.…”
Section: Resultsmentioning
confidence: 99%
“…The midlatitude S q current intensity during solar maximum is approximately twice as high as that during solar minimum [ Takeda , ]. The amplitude and phase of seasonal S q variations are also modulated by solar activity [ Yamazaki and Yumoto , ; Çelik et al , ]. The solar activity dependence of S q variations is mainly due to enhanced ionospheric conductivities during high solar activity periods, which lead to increased ionospheric currents [ Takeda et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…These trends were attributed to solar extreme ultraviolet (EUV) radiation changes (Adler et al 1997;Yamazaki and Yumoto 2012), geomagnetic activity variations (Mikhailov and Marin 2001;Danilov 2002;Mikhailov 2001Mikhailov , 2006, the increase in greenhouse gas concentration (Bremer 1992(Bremer , 1998Upadhyay and Mahajan 1998;Ulich and Turunen 1997;Jarvis et al 1998), and/or secular variations of the Earth's main magnetic field (Foppiano et al 1999;Elias and Adler 2006;Elias 2009;Yue et al 2008;Richmond 2008, 2013;Cnossen et al 2012).…”
Section: Introductionmentioning
confidence: 99%